Study protocol of RESCUE-ALS: A Phase 2, randomised, double-blind, placebo-controlled study in early symptomatic amyotrophic lateral sclerosis patients to assess bioenergetic catalysis with CNM-Au8 as a mechanism to slow disease progression - William Huynh (BMJ Publishing Group, 2021)
Introduction Amyotrophic lateral sclerosis (ALS) is an adult-onset, progressive and universally fatal neurodegenerative disorder. In Europe, Australia and Canada, riluzole is the only approved therapeutic agent for the treatment of ALS, while in the USA, riluzole and edaravone have been approved by the Food and Drug Administration (FDA) . Neither riluzole nor edaravone treatment has resulted in substantial disease-modifying effects. There is, therefore, an urgent need for drugs that result in safe and effective treatment. Here, we present the design and rationale for the phase 2 RESCUE-ALS study, investigating the novel nanocatalytic drug, CNM-Au8, as a therapeutic intervention that enhances the metabolic and energetic capacity of motor neurones. CNM-Au8 is an aqueous suspension of clean-surfaced, faceted gold nanocrystals that have extraordinary catalytic capabilities, that enhance efficiencies of key metabolic reactions, while simultaneously reducing levels of reactive oxygen species. This trial utilises a novel design by employing motor unit number index (MUNIX), measured by electromyography, as a quantitative measure of lower motor neurone loss and as an early marker of ALS disease progression.Methods and analysis This is a multicentre, randomised, double-blind, parallel group, placebo-controlled study of the efficacy, safety, pharmacokinetics and pharmacodynamics of CNM-Au8 in ALS patients. Patients will be randomised 1:1 to either receive 30 mg of CNM-Au8 once daily or matching placebo over a 36-week double-blind treatment period. Efficacy will be assessed as the change in motor neurone loss as measured by electromyography (eg, MUNIX, the primary endpoint; and secondary endpoints including MScanFit, motor unit size index, Split Hand Index, Neurophysiology Index). Exploratory endpoints include standard clinical and quality of life assessments.Ethics and dissemination RESCUE-ALS was approved by the Western Sydney Local Health District Human Research Ethics Committee (Ethics Ref: 2019/ETH12107). Results of the study will be submitted for publication in a peer-reviewed journal.Trial registration number NCT04098406